Indicadores chave de desempenho em restaurantes: visão dos gestores no segmento de pequenas e médias empresas. - MOREIRA, Aline de Godoy (2017)
The F&B Industry, particularly the restaurant industry, has demonstrated its competitive capacity by imposing the need to provide quality customer retention services. Among the challenges faced by its entrepreneurs is the demand for greater professionalization of management, especially by small and mediumsized companies (SMEs). However, there are few or no empirical researches that present data on how managers manage their businesses, as well as literature on the subject. In order to contribute to fill this information gap, it was established as a general objective of this dissertation to understand the main performance indicators that contribute to the success and continuity of SME restaurants, taking as a point of view the design of the restaurant managers compared to the proposed by the literature on the subject. For this study, the following research propositions were established: (a) restaurant managers will present as indicators more relevant to the success of the CMV (Cost of Goods Sold), CMO (Labor Cost), Prime Cost and Index of Profitability; (b) The groups of indicators of the area of management of finance and administration will be considered the most relevant to the success of the enterprise; c) Managers will be reluctant to talk about their business making it difficult to collect data. As a methodological procedure, the study was based on two phases, the first exploratory bibliographical and the second empirical. The phase indicated that there are no empirical studies on the subject; thus, the most cited criteria were selected for the purpose of elaborating a research instrument to meet the general objective of the dissertation. In the empirical phase, the collection was done through a survey applied to the restaurant managers through electronic means, specialized mailings and personal visit of the researcher to establishments to interview their managers. During collection, the greatest obstacle in obtaining a significant sample was revealed. There was great resistance from managers, both in responding the questionnaires and during personal views, in talking about their business. At the end it was reached the number of 49 (forty-nine) establishments. However, the results were sufficient to confirm the three propositions of the research and consolidate an suitable instrument to be applied in other situations, which is the major contribution of this dissertation. Among other results we can indicate: the grouping of the indicators into 8 factors, so-called: Results Evaluation, Revenue, Attendance, Clients, Average Cost of Production, Manpower, Controls and Management of Bars. The Factor of Results, containing the indicators: Technical Sheets / Selling Price; Turnover or Turnover Rate; Menu Engineering; DRE - Statement of Results for the Year and Percentage of return on marketing actions developed, obtained 35% of the variance explained, and can be considered the most relevant in the managers' conception.